A critical review of high polymer-modified asphalt binders and mixtures. Issue Volume 21:Issued 6(2020) (11th May 2020) - Habbouche, Jhony; Hajj, Elie Y.; Sebaaly, Peter E.; Piratheepan, Murugaiyah
ABSTRACT: The introduction of modified asphalt binders provided transportation agencies an effective tool to design balanced mixtures that can resist conflicting distresses while maintaining good long-term durability. While conventional polymer modified asphalt mixtures have shown improved long-term performance, it is also believed that asphalt mixtures with high polymer (HP) content may offer additional advantages in flexible pavements subjected to heavy and/or slow moving traffic loads. While no unique and detailed handy guide that discusses the HP modification of binders and mixtures exists at this time, and while asphalt industry is moving towards the use of much more durable materials for a better long-term performance of newly constructed roads, this manuscript summarizes the findings from the literature review on the performance of HP asphalt binders and mixtures. The reviewed laboratory studies indicated that the increase in polymer content continues to improve the performance properties of binders and mixtures. The reviewed field projects showed encouraging early field performance without exhibiting any construction related issues. In addition, this article presents attempts that were explored to estimate a structural coefficient of HP mixes based on the available information from literature. This analysis led to the conclusion that the designed HP mixtures may lead up to 40% reduction in the asphalt layer thickness resulting in considerable upfront cost-savings.